2022
DOI: 10.3892/ijo.2022.5447
|View full text |Cite
|
Sign up to set email alerts
|

Realgar‑induced KRAS mutation lung cancer cell death via KRAS/Raf/MAPK mediates ferroptosis

Abstract: KRAS is a biomarker for non-small cell lung cancer-targeted therapy, but there is currently no effective KRAS-targeting medication. Realgar is an impelling anticancer drug, however its significance in KRAS mutant lung cancer is uncertain. According to our findings, the IC 50 of H23 (KRAS mutant) cells is 2.99 times lower than that of H1650 (non-KRAS mutant) cells. Flow cytometry and the Hoechst 33258 staining assay revealed that H1650 cells treated with 4 µg/ml realgar had an apoptotic rate of 8.2%, while H23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For example, Liu et al evaluated the cytotoxicity of realgar in 4 types of NSCLC cell lines, including H23, A549, H460 and H1650. They demonstrated that realgar could induce apoptosis and inhibit the proliferation of NSCLC cells via inducing ferroptosis by KRAS/Raf/MAPK pathway [ 36 ]. Another study revealed that realgar inhibited the viability as well as the glucose consumption of lung cancer stem cells isolated from NSCLC cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al evaluated the cytotoxicity of realgar in 4 types of NSCLC cell lines, including H23, A549, H460 and H1650. They demonstrated that realgar could induce apoptosis and inhibit the proliferation of NSCLC cells via inducing ferroptosis by KRAS/Raf/MAPK pathway [ 36 ]. Another study revealed that realgar inhibited the viability as well as the glucose consumption of lung cancer stem cells isolated from NSCLC cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the caenorhabditis elegans model, realgar, a sulfide mineral from ores, downregulates Ras expression through the Ras/MAPK signaling pathway [105]. Further studies reveal Realgar's potential to inhibit KRASmutated lung cancer cell growth by inducing ferroptosis via the Raf-mediated Ras/MAPK pathway [106], positioning it as a promising anti-cancer agent, especially for Ras mutation-targeted ferroptosis.…”
Section: Beas-2b Cellsmentioning
confidence: 99%
“…For example, in the context of focal cerebral ischemia, ACSL4 is upregulated in a microRNA (miR-347)-dependent manner, consequently promoting neuronal apoptosis [ 95 ]. Additionally, ACSL4 directly interacts with and regulates proteins involved in apoptotic signaling pathways [ 96 ]. Thus, ACSL4 has a dual role in apoptosis: it can inhibit apoptosis by promoting fatty-acid oxidation, leading to increased phospholipid synthesis and chemoresistance, and it can promote apoptosis by producing lipid-free radicals and directly regulating apoptotic signaling pathways.…”
Section: Acsl4 In Apoptosismentioning
confidence: 99%